2020
DOI: 10.1109/access.2020.3028941
|View full text |Cite
|
Sign up to set email alerts
|

Design Method of 6-Element Boundary Gain for LLC Resonant Converter of Electric Vehicle

Abstract: In the application of on-board chargers, LLC resonant converters need to work in multiple operating modes to achieve wide-range output requirements. For the most commonly used single-phase and three-phase LLC topologies, the time domain expressions of all possible operating modes are introduced to predict voltage and current behaviors. Based on the mode analysis, the 6-element boundary gain design method is proposed to design a wide gain range LLC resonant converter. The resonant current is used as the basis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Figure. 19 indicates the switching ON process of S5, S6, which conduct to boost up the output voltage. Benefits from the primary control, zero-current detection is unnecessary to outset the higher voltage power transmission.…”
Section: B Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure. 19 indicates the switching ON process of S5, S6, which conduct to boost up the output voltage. Benefits from the primary control, zero-current detection is unnecessary to outset the higher voltage power transmission.…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…It concluded that the accuracy of FHA is higher when the system operates under a low quality factor and near the compensated resonant frequency. FHA has been widely examined and used in many applications, included the closed-loop control converter, bidirectional DC-DC converter, wide output vehicle chargers with power factor correction, and waterproof vessel wireless charger due to the high accuracy, simple design process, and control strategy [19][20][21][22][23]. Many subtle control methods such as the closed-loop design and the frequency doubler method to raise the output power based on FHA have been investigated in LLC non-WPT system area [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…A half-bridge LLC converter, as shown in Fig. 5 (a), can achieve a 10kW bidirectional power flow with 96% efficiency when it is controlled with a variable switching frequency [105]- [107]. A variable DC-link voltage of the AC/DC converter can maximize the efficiency of secondend stage.…”
Section: B Dc/dc Convertersmentioning
confidence: 99%
“…In this two-stage converter, a boost AC-DC converter is used as a power factor correction (PFC) module to isolate harmonic pollution from the grid and provide pure supply of direct voltage to the next stage module. In addition, an isolated DC/DC converter is used to directly handle complex load conditions to accommodate the linear load characteristics and wide adjustable output voltage range of the EV's high-voltage battery [9]. Therefore, the characteristics of this two-stage converter are largely influenced by the DC/DC converter, which means that the design of the DC/DC converter is particularly important for off-board chargers.…”
Section: Introductionmentioning
confidence: 99%